2021
DOI: 10.1111/jpn.13488
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Echinacea purpurea administration enhanced egg laying performance, serum lipid profile, antioxidant status and semen quality in duck breeders during summer season

Abstract: This work investigated the outcomes of dietary administration of Echinacea purpurea (EP) powder to breeder ducks on productive and reproductive performance during summer season. Sudani ducks (320 birds) of 32‐weeks‐old (240 females and 80 males) were randomly allocated into four collections (body weight; 1850 ± 15.2 g for females and 2960.0 ± 40.5 g for males). The primary collection consumed the basal diet without supplementation and was deliberated as control. The other three collections were fed the basal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…1 Price of one Kg/live body weight on selling was USD 3.19. 2 Net revenue = Price of rabbit (USD)-Total feed cost (USD). 3 Economic efficiency = Net revenue/Total feed cost (USD).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Price of one Kg/live body weight on selling was USD 3.19. 2 Net revenue = Price of rabbit (USD)-Total feed cost (USD). 3 Economic efficiency = Net revenue/Total feed cost (USD).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there has been growing interest in using natural feed additives to enhance animal performance and meat quality for human consumption [1][2][3][4]. Water-soluble vitamins such as vitamin C (L-ascorbic acid or simply ascorbate) are normally synthesized by the rabbit digestive flora and the dietary supplementation of 25-30 mg/rabbit/day may be advisable in cases of the digestive disorders, as after weaning [5].…”
Section: Introductionmentioning
confidence: 99%
“…Santoso et al [57] reported that supplementation 5% addition of papaya leaf extract can improve body weight gain and carcass quality in broiler chickens, and increase egg protein content. The scientific literature contains also numerous reports indicating that phytobiotics do not significantly affect growth performance, feed conversion ratio and the survival rate of poultry but regulate the physiological functions of the organism (metabolism, activity of important enzymes, the level of minerals or blood composition) [5,58,59].…”
Section: The Influence Of Phytobiotics On the Processes Taking Place In The Birds' Organism 21 The Influence Of Phytobiotics On Growth Anmentioning
confidence: 99%
“…Proceeded antibiotics uses in modern poultry industry could to increment disease resistance, however preventing, restricting or decreasing their uses might induced to undesirable changes, particularly on conversion efficiency (Awad et al, 2021). Increased consumer attention with health problems, as well as craving to restrict or forestall antibiotics uses for their adverse consequence, the insiders in poultry industry are compelled for look a nature replacements proverb phytogenic feed additives so as to help the challenge of poultry diseases in their farms.…”
Section: Introductionmentioning
confidence: 99%
“…Also, using YS could be diminish NH3 concentration in farms that reflect improving the poultry productivity (Ayasan et al, 2005). Ducks are kept under intense farming in greatly occupied herds to achieve huge intensities of economic value as it is one of the tremendously successful and rapid generating business that provides great protein (Farghly et al, 2017;Awad et al, 2021). Thus, the chief purposes of the contemporary investigation were to assess the impact of dietary dried YS addition on ducks productivity, hatching measurements and blood parameters at summer time.…”
Section: Introductionmentioning
confidence: 99%